Difficult-to-treat women for controlled ovarian hyperstimulation: tips and tricks. Issue 4 (July 2011) - Artini, Paolo Giovanni; Papini, Francesca; Ruggiero, Maria; Scaravelli, Giulia; Di Berardino, Olga Maria; Simi, Giovanna; Cela, Vito
The aim of this article is to clarify the different strategies used to induce controlled ovarian hyperstimulation in some groups of difficult-to-treat patients, namely poor-responder patients, polycystic ovarian patients and endometriosis patients. The success of in vitro fertilization depends on adequate follicle recruitment and the recovery of multiple good-quality oocytes by using controlled ovarian hyperstimulation. This is particularly difficult to achieve in patients with a high incidence of low ovarian response (stage III––IV endometriosis and premature ovarian failure patients) or an excessive ovarian response with a risk of ovarian hyperstimulation syndrome (polycystic ovary syndrome patients). Consequently, special methods are needed in these groups of patients in order to optimize in vitro fertilization results.